Investigation of Interaction Effects of Elbow and Wrist Angles in Sitting and Standing Postures on Grip Strength and Perceived Exertion - Davood Afshari; Niloofar Chinisaz; Maryam Seyedtabib; Iman Dianat; Maryam Nourollahi-Darabad (بهداشت و ایمنی کار)
Introduction: Biomechanical risk factors, including wrist and elbow angle and standing and sitting position, are the primary factors affecting hand grip strength and perceived exertion. The interaction of these factors can include different effects on grip strength and perceived exertion. Therefore, the present study examines the interaction of varying wrist and elbow angles in sitting and standing postures on the variability of grip strength and perceived exertion. Material and Methods: In the present study, 30 students (15 females, 15 males) aged 19-30 participated. The average grip strength was measured by a dynamometer for 12 different positions based on the angle of the wrist and elbow in both standing and sitting postures. Perceived exertion was also assessed using the Borg CR-10 scale for each setting. Data analysis was performed using SPSS 23. The Wilcoxon test was applied to compare perceived exertion between standing and sitting postures. Furthermore, a three-way ANOVA was performed to examine interactions between posture (standing/sitting), elbow, and wrist angles. Mauchly’s Sphericity Test was applied to confirm the ANOVA assumptions, and effect sizes for multivariate analysis were calculated (partial η2). Results: In both sitting and standing postures, the highest average grip strength was observed at a 0-degree wrist angle with a 90-degree elbow angle (standing: 28.6 ± 10.8, sitting 25.8 ± 9.8), while the lowest average grip strength was recorded at full wrist extension with a 0-degree elbow angle (standing: 19.3 ± 6.5, sitting 17.9 ± 6.9). In all three elbow angles examined (0°, 60°, and 90°), the highest value of perceived exertion was recorded in the full extension of the wrist. The changes in the grip strength at different angles were the same for sitting and standing postures, yet the hand grip strength was higher in the standing than the sitting posture (P-value<0.001). The effect of each of the studied factors (sitting and standing postures, wrist angle, and elbow angle) alone on hand grip strength and perceived exertion was deemed to be significant (P-value<0.001). Regarding the two-way interactions of the research variables, the interaction effect of elbow and wrist angles on grip strength (partial η2=0.09, P-value=0.015) and perceived exertion was significant (partial η2=0.08, P-value=0.06). Furthermore, findings indicated that the wrist angle had a more pronounced effect on the value of the perceived exertion (partial η2=0.31, P-value<0.001).